Rede overlay de suporte a ambientes virtuais colaborativos em redes veiculares - Meneguette, Rodolfo Ipolito (2009)
Collaborative Virtual Environments (CVEs) are synthetic 3D environments shared by multiple remotely located users with a common goal: the access to the environment through avatars (graphical representations of the user). CVEs are becoming popular on mobile devices such as handheld devices and cell phones, through games and simulations for users entertainment and comfort. These virtual environments require low latency and high scalability so that a large number of participants can interact in a consistent way without losing the immersion feeling. Therefore it entails a major concern on participants s connection strategies, especially when these environments are implemented on moving vehicles, because the unique characteristics of a vehicular ad hoc network (VANETs) like high mobility of nodes, high speed transmission and a highly dynamic topology demand a complex structure to overcome these limitations. These characteristics lead us to communication challenges among participants and to the dissemination of actions results of their avatars in the CVE and / or the state change of an object for all participants. The communication support network should be able to cope with the entrance of an increasing number of participants in the CVE without affecting these users feeling of presence. In order to overcoming the challenges of scalability and ensuring a uniform view of the virtual world for all users in VANETs networks, this paper presents a design and evaluation of an overlay network, specifically a peer-to-peer (p2p) network, which aims at providing connectivity between users of a CVE, in addition to updating the status of avatars and objects in the CVE for all participants, ensuring that information is delivered in the shortest time possible.